Fertility after expanded polytetrafluoroethylene use after endometrioma cystectomy: a pilot study - Yeung, Patrick P.; Su, Melody S.; Voltz, John; Gavard, Jeffrey A. (Frontiers in Reproductive Health, 2023)
Introduction Pregnancy rates after the placement of expanded polytetrafluoroethylene (ePTFE, trade name Gore-Tex®) for adhesion prevention following cystectomy of endometriomas ≥3 cm and excision of endometriosis were analyzed in this pilot study. Methods A prospective cohort study was performed at a single tertiary care center. 56 women qualified for the study and underwent surgery. Expanded polytetrafluoroethylene placement around affected ovaries was self-selected. Inclusion criteria for analysis were pathology-confirmed endometrioma ≥3 cm, no hysterectomy at time of surgery, ≥1 year of postoperative survey completion, and absence of strategies to avoid pregnancy. 18 women in the ePTFE group and 11 women in the control group met inclusion criteria for analysis. 16 of the 18 women in the ePTFE group and 7 of the 11 women in the control group were affected by infertility. Absolute pregnancy rates and cumulative 4-year pregnancy rates, which are based on survival analysis using lifetables and adjust for varying follow-up times, were calculated for all women as well as for women with infertility only. Results High cumulative 4-year pregnancy rates were observed for women with expanded polytetrafluoroethylene compared to women without (85% vs. 65%, p = 0.69). High cumulative 4-year pregnancy rates for women with infertility prior to surgery were observed for women with expanded polytetrafluoroethylene compared to women without (83% vs. 33%, p = 0.89). Discussion There are consistent trends, although not statistically significant, seen in pregnancy rates for women with ePTFE compared to women without, particularly in those with a history of infertility prior to ePTFE use. This is the first study examining how adhesion prevention strategy targeting the adnexa during surgery for endometriosis affects pregnancy rates. The trend towards increased pregnancy rates with expanded polytetrafluoroethylene use, particularly in patients with a history of infertility, is promising and warrants further study with larger groups.